Gamification and neurological motor rehabilitation in children and adolescents: a systematic review - Pimentel-Ponce, María; Romero-Galisteo, Rita Pilar; Palomo‐Carrión, Rocío; Pinero‐Pinto, Elena; Merchán‐Baeza, José Antonio; Ruiz-Muñoz, María; Oliver-Pece, Jesús; González-Sánchez, Manuel (Elsevier, 2024)
Introduction: Gamification consists of the use of games in non-playful contexts. It is widely employed in the motor rehabilitation of neurological diseases, but mainly in adult patients. The objective of this review was to describe the use of gamification in the rehabilitation of children and adolescents with neuromotor impairment. Methods: We performed a systematic review of clinical trials published to date on the MEDLINE (PubMed), Scielo, SCOPUS, Dialnet, CINAHL, and PEDro databases, following the PRISMA protocol. The methodological quality of the studies identified was assessed using the PEDro scale. Results: From a total of 469 studies, 11 clinical trials met the inclusion criteria. We analysed the gamification systems used as part of the rehabilitation treatment of different neuromotor conditions in children and adolescents. Cerebral palsy was the most frequently studied condition (6 studies), followed by developmental coordination disorder (3), neurological gait disorders (1), and neurological impairment of balance and coordination (1).Conclusion: The use of gamification in rehabilitation is helpful in the conventional treatmentof neuromotor disorders in children and adolescents, with increased motivation and therapeu-tic adherence being the benefits with the greatest consensus among authors. While strength,balance, functional status, and coordination also appear to improve, future research shouldaim to determine an optimal dosage
Keywords: Enfermedades neurológicas - Rehabilitación; Adolescent; Child; Neurological Rehabilitation; Systematic Review; Video game